Kinematic Differences in the Roundhouse Kick among University Taekwondo Players: Brief Report - Raúl Josue Nájera-Longoria; Omar Ricardo Ortiz-Gómez; Samuel Alfredo Islas-Guerra; Arturo Iván Chávez-Erives; Arturo Martínez-Trevizo; Víctor Hugo López-Trujillo; Mario Armando Amorós Gómez (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2024)
This study aimed to investigate the bilateral kinematic differences in temporal variables between the Dominant and Non-dominant legs in the roundhouse kick of college-level women practicing Taekwondo. Four male athletes with black belts volunteered to participate in the study. Participants were instructed to perform five kicks with each leg after visual stimuli at maximal velocity allowing 30-s passive recovery time between each kick. Reaction time, movement time, and attack time in the roundhouse kick were assessed using video cameras and force platforms for both the dominant and non-dominant legs. The analysis revealed no significant differences in reaction times (0.15 ±0.03 and 0.15 ±0.04 s, n=20), movement times (0.62 ±0.06 and 0.64 ±0.04 s, n=20), or attack times (0.77 ±0.09 and 0.79 ±0.06 s, n=20) for the dominant and non-dominant legs (p>0.05). However, a bilateral dominance was observed, consistent with the sporting level of the participants. These results support the training regimen both-guards oriented equally to improve overall performance in Taekwondo.